2018
DOI: 10.1002/ijc.31747
|View full text |Cite
|
Sign up to set email alerts
|

Rising rates of bilateral mastectomy with reconstruction following neoadjuvant chemotherapy

Abstract: Neoadjuvant chemotherapy is used to allow more limited breast surgery without compromising local control. We sought to evaluate nationwide surgical trends in patients with operable breast cancer treated with neoadjuvant chemotherapy and factors associated with surgical type. We used the National Cancer Database to identify 235,339 women with unilateral T1–3N0–3M0 breast cancer diagnosed between 2010 and 2014, and treated with surgery and chemotherapy. Of these, 59,568 patients (25.3%) were treated with neoadju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The rate of contralateral prophylactic mastectomy has more than doubled in the past decades, with a similar trend in immediate reconstruction. [1][2][3][4][5][6][7] Patients with no proven genetic predisposition also opt for this elective operation likely due to cancer-related anxiety, despite the lack of evidence for a survival benefit. 1 , 8 , 11 , 21-23 The availability of reconstruction appears to influence patient decision-making 6 , 7 , 12 , 15 , 24 , 25 , and there is evidence of higher patient satisfaction and superior long-term cosmetic outcome with bilateral implantbased reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of contralateral prophylactic mastectomy has more than doubled in the past decades, with a similar trend in immediate reconstruction. [1][2][3][4][5][6][7] Patients with no proven genetic predisposition also opt for this elective operation likely due to cancer-related anxiety, despite the lack of evidence for a survival benefit. 1 , 8 , 11 , 21-23 The availability of reconstruction appears to influence patient decision-making 6 , 7 , 12 , 15 , 24 , 25 , and there is evidence of higher patient satisfaction and superior long-term cosmetic outcome with bilateral implantbased reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with unilateral diagnosis of breast cancer increasingly elect to undergo bilateral mastectomies. [1][2][3][4][5][6][7] Even though the risk of contralateral breast cancer is low in the absence of a genetic mutation, patient misperceptions of the true benefits of a contralateral prophylactic mastectomy might account for this increase. 1 , 8 , 9 Young patient age, Caucasian ethnicity, higher education level, family history, and positive genetic testing have been shown to be predictors of prophylactic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…A recent NCDB-based study reported similar results following the evaluation of almost 60,000 women submitted to NACT between 2010 and 2014. 24 Despite the increase in full pathological response over the time period, the rates of breast conservation increased slightly from 37.0% to 40.8% (p = 0.22) and bilateral mastectomy rates with immediate breast reconstruction increased from 8% to 13.1%, with a reduction in unilateral mastectomy. In the present study, bilateral surgery increased for patients with aggressive chemosensitive disease (70% of HER2 and 67% of the TN cases), although they would normally be potential candidates for NACT and conservative surgeries.…”
Section: Discussionmentioning
confidence: 90%
“…With the rates of mastectomy for both oncologic and prophylactic needs rising (Pollom et al, 2018), breast reconstruction remains a bedrock procedure for plastic surgeons. Given the improved aesthetic outcomes and satisfaction rates, patients are consistently opting to undergo free flap breast reconstruction rather than implant-based reconstruction, if they are a candidate (Pirro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%